Elicited Subject-Verb Agreement in German Early L2 Children with Developmental Language Disorders. (18th December 2019) - Scherger, Anna-Lena
The present study investigates whether subject-verb agreement (SVA) serves as a clinical indicator for developmental language disorders (DLD) in early second language learning (eL2) children. Using a LITMUS-tool (language impairment testing in multilingual settings) described by de Jong (2015 ) for eliciting SVA contexts, 22 German eL2 children aged six to eight years with and without DLD are tested for their ability to mark SVA in first-, second- and third-person singular forms of transitive verbs. Results show significant differences between eL2 children with and without DLD. Other factors shaping the eL2 acquisition process, namely age of onset, length of exposure, first language and the amount of second-language German input at home, do not appear to have a significant influence on the total SVA marking. However, some of the children with DLD in this age bracket have already mastered the German SVA paradigm. It is thus concluded that SVA is a reliable indicator of DLD in most cases. However, due to its diagnostic accuracy of 82% it should not be used as a screening on its own but must always be accompanied by the investigation of later acquisition phenomena in order to avoid underdiagnoses.